2017
DOI: 10.15448/1983-652x.2017.2.23297
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de Toxoplasma gondii em gestantes atendidas pelo Sistema Único de Saúde

Abstract: Exceto onde especificado diferentemente, a matéria publicada neste periódico é licenciada sob forma de uma licença Creative Commons BY-NC 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 6 publications
1
3
0
3
Order By: Relevance
“…Positive seroprevalence is more relevant after 31 years of age, according to the literature, which was confirmed in this study. Seroprevalence in those older than 30 years represented the majority of infections in our study (64.2%), and in other national studies (59,8%, 45%, 74,5% and 68,7%, respectively) 20, [22][23][24] . The seroprevalence of T. gondii is higher in older people than younger people, due to the longer exposure time, so they are more susceptible to contamination by the different infective forms of T. gondii 25,26 .…”
Section: Discussionsupporting
confidence: 78%
“…Positive seroprevalence is more relevant after 31 years of age, according to the literature, which was confirmed in this study. Seroprevalence in those older than 30 years represented the majority of infections in our study (64.2%), and in other national studies (59,8%, 45%, 74,5% and 68,7%, respectively) 20, [22][23][24] . The seroprevalence of T. gondii is higher in older people than younger people, due to the longer exposure time, so they are more susceptible to contamination by the different infective forms of T. gondii 25,26 .…”
Section: Discussionsupporting
confidence: 78%
“…Studies conducted in Brazil concluded that the lack of information about the disease was the most relevant factor for seroprevalence, directly reflecting the higher transmission of the disease, proving that sensitization campaigns should be conducted to prevent the spread of toxoplasmosis. 23 From the detection of acute disease the treatment begins, which is not fully effective to prevent transplacental transmission of the parasite, besides being composed of drugs with teratogenic effects. It is important to emphasize that there is currently no treatment for the chronic phase of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Dados demonstram que medidas profiláticas executadas durante a gestação podem diminuir a contaminação fetal em mulheres susceptíveis à infecção por T. gondii (Nascimento et al, 2017). Resultados de uma pesquisa brasileira indicaram que a falta de informações sobre a doença foi o fator mais relevante para a alta soroprevalência da toxoplasmose, devido à maior transmissão da doença, comprovando que as campanhas de sensibilização devem ser realizadas para evitar o aumento de toxoplasmose (Nascimento et al, 2017).…”
Section: Discussionunclassified
“…Dados demonstram que medidas profiláticas executadas durante a gestação podem diminuir a contaminação fetal em mulheres susceptíveis à infecção por T. gondii (Nascimento et al, 2017). Resultados de uma pesquisa brasileira indicaram que a falta de informações sobre a doença foi o fator mais relevante para a alta soroprevalência da toxoplasmose, devido à maior transmissão da doença, comprovando que as campanhas de sensibilização devem ser realizadas para evitar o aumento de toxoplasmose (Nascimento et al, 2017). Outros trabalhos realizados também no Brasil, demonstraram que a maioria das gestantes consultadas não receberam orientações sobre a doença durante o pré-natal, e que o desconhecimento dessas gestantes sobre a toxoplasmose reflete a falta de orientações vindas dos profissionais de saúde durante as consultas.…”
Section: Discussionunclassified